Da'i Challenges in Preaching to Muslim Minority Communities in Kutalimbaru Village, Deli Serdang - Muktarruddin; Abdul Rahman Pais Nasution; Siti Annisa Marsanda; Nandini; Muhammad izwan (MAQOLAT: Journal of Islamic Studies, 2023)
The challenge of da'wah is what a da'i will face later when carrying out da'wah in any era. It also means preaching in the era of minority Muslim communities. This challenge does not only come from the environment, but even face to face. Taking the wrong step will cause a conflict when visiting the village to be visited. That's why the preachers before preaching must first go to the place and see what the people who will be preached about are like that can see what must be avoided so that something unwanted doesn't happen. It is important to look at the aspects contained in the environment, so that it does not offend the people of Kutalimbaru village. Da'wah there by teaching them what they need. Because, the delivery of da'i messages must be in accordance with what is needed. The people in Dusun 1 village of Kutalimbaru have a strong passion to gain knowledge. However, the narrow network results in limitations in religious knowledge so that what is forbidden to do or touch they do and casually tell the volunteers that's the children there who need special education to be able to get religious learning.